Seruling “SERULING” PROGRAM FOR EMPOWERING THE VILLAGE OF NANGGALAMEKAR VILLAGE BASED ON ENVIRONMENTAL ARTS - Agus Cahyana; Nani Sriwardani (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
Nanggalamekar Village is located in Ciranjang District, Cianjur Regency. However, at this time there has been a change of land function, from agricultural land to sand excavation and settlements, this has an impact on the occurrence of damage to the natural environment and eliminates many livelihoods related to nature. Based on these problems, the Environmental Arts program (SERULING) was developed which is aimed at increasing public awareness about the importance of preserving the environment and empowering the potential of nature that is environmentally friendly. The method used to run this program is Participation Action Research (PAR) which makes village communities the main actors in this service activity. Meanwhile, the implementation refers to the KUPAR stages, namely to Know, to Understand, to Plan, to Action and to Reflection. With these stages, the training and mentoring carried out can be in accordance with what is needed by the community and be able to optimize the potential of existing resources in the village. The results of the training are environmental art products in the form of monumental art models for tourist attractions and ornamental products from natural materials as decorative objects or other functional objects that are able to be a solution for improving the welfare of rural communities as well as being a learning medium to increase public awareness of the environment.